Fish Consumption, Exposure to Dioxin, and Health Risk Assessments - Boyle, Kevin (Maine Policy Review, 1994)
Human health issues have become the focus of much of the environmental debate that continues to occur daily in theU.S.InMaine, dioxin, a by-product of the kraft paper making process, has gathered its share of attention in recent months.UniversityofMaineresource economist Kevin Boyle discusses the difficulties associated with assessing human health risks relative to the consumption of fish tissue potentially contaminated with dioxin. He cautions state regulators to avoid overestimating the potential risks associated with human exposure to toxic substances such as dioxin.